Sinergi MNC University, SHARP Class, dan SMK Boedi Luhur dalam Pengembangan UMKM - Ariawan, Angga; Rizki, Sestri Novia; Herdadi, Anintyo (ASOSIASI IDEBAHASA KEPRI, 2025)
The development of Micro, Small and Medium Enterprises (MSMEs) is one of the strategic efforts to encourage local and national economic growth. However, low technological literacy and data analytical capabilities are the main obstacles for MSMEs in facing competition in the digital era. To answer these challenges, MNC University, in collaboration with the SHARP Class Corporate Social Responsibility (CSR) program from PT SHARP Electronics Indonesia, as well as Boedi Luhur Bekasi Vocational School, is implementing a technology-based community service program. This program focuses on providing data analytics skills to vocational school students as young people who have the potential to support MSMEs in their surrounding environment. This activity includes intensive training on data processing using computer science-based tools and methods, designed to improve students' ability to understand, analyze and apply data in making business decisions. A collaborative approach involving academics, industry practitioners and vocational educators ensures that the material presented is relevant to the needs of industry and MSMEs. The results of this program show a significant increase in participants' understanding and skills in data analytics, as well as the real contribution of Boedi Luhur Vocational School students in supporting the development of local MSMEs. This study provides empirical evidence that synergy between educational institutions, industry and vocational schools can be a model of sustainability in developing technology-based human resource capacity.